Fairness and Redistribution: Reply - Alesina, Alberto; Angeletos, George-Marios; Cozzi, Guido (American Economic Review, 2013)
This paper responds to the comment of Di Tella and Dubra (2013). We first clarify that the model of Alesina and Angeletos (2005) admits two distinct types of multiplicity: one that is at the core of their contribution, and a separate one that is at work in Di Tella and Dubra's example. We then proceed to show how Alesina and Angeletos's results are robust to alternative specifications of the voting mechanism.